Technical Feasibility, Short-Term Patency, Safety, and Efficacy of Percutaneously Delivered Double Pig-Tail Stent for Palliation of Unresectable Biliary Malignancies - Ashish Verma; Ishan Kumar; Pramod Kumar Singh; Tarun Kumar; Durgatosh Pandey (Journal of Clinical Interventional Radiology ISVIR)
Purpose The aim of this study was to evaluate the technical feasibility, complication rate, and efficacy of percutaneously delivered plastic biliary stent, compared with that of internal–external biliary drainage catheter.